Quality of Life of Patients submitted to Total Knee Arthroplasty - da Silva, Robson Rocha; de Souza, Silmara Ramos; Castro, Martha Moreira; Matos, Marcos Almeida; Ariel de Lima, Diego (Journal of Health & Biological Sciences, 2024)
Objective: the aim of this study was to evaluate the quality of life between patients who have already undergone the TKA surgery and those who have not. Methodology: 118 patients [60 undergoing TKA (G1) and the remaining 58 awaiting the procedure (G2)] answered questions about QoL using the WOMAC and SF-36 protocols. The comparison was performed using the chi-square test and Student's t-test, with a significance level of 0.05. Results: with regard to clinical aspects, there was a higher level of pain in Group G2, as well as greater frequency in the use of medications, especially for pain relief. In the QoL evaluation, significant difference was observed in all the domains of the generic questionnaire SF-36 and in WOMAC, estando a capacidade functional do G2 reduzida e abaixo do nível observado nos pacientes do G1. Conclusion: patients with advanced knee arthrosis who underwent TKA, compared to those who did not undergo the procedure, had better quality of life in all domains assessed by both the general SF-36 questionnaire and the WOMAC questionnaire.